Analisis Penetapan Harga Pokok Penjualan Dengan Menggunakan Metode Rata-Rata (Average) Dalam Pengendalian Persediaan Barang (Studi Pada Toko Mulya Tani) - Azkiya Awaliah; Muhammad Yamin; Andi Patimbangi (Journal of Mandalika Literature, 2025)
This thesis discusses the analysis of determining the cost of goods sold using the average method in controlling inventory at the Mulya Tani Store. The purpose of this study is to determine the use of the average method in determining the cost of goods sold in controlling inventory at the Mulya Tani Store. The type of research used in this study is field research and seen from the data analysis, this research is a qualitative study. Data collection techniques through interviews, observation, and documentation. Data analysis used is qualitative data analysis with the stages of data reduction, data presentation and presentation of conclusions. The study shows that the use of the average method in determining the cost of goods sold at the Mulya Tani Store has a positive impact on inventory control and operational efficiency. This method simplifies the recording of incoming and outgoing goods, simplifies the calculation of COGS, and helps maintain the stability of selling prices amidst fluctuations in purchasing prices from suppliers. Although recording is still done manually due to the limited technological knowledge of the owner, this method is considered practical and appropriate for the type of business being run. Both the owner and employees agree that this method facilitates reporting, purchasing planning, and staff training.